2022
DOI: 10.3390/cells11091533
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Fast-Scan Cyclic Voltammetry to Explore Dopamine Dynamics in Animal Models of Neuropsychiatric Disorders

Abstract: Progress in the development of technologies for the real-time monitoring of neurotransmitter dynamics has provided researchers with effective tools for the exploration of etiology and molecular mechanisms of neuropsychiatric disorders. One of these powerful tools is fast-scan cyclic voltammetry (FSCV), a technique which has progressively been used in animal models of diverse pathological conditions associated with alterations in dopamine transmission. Indeed, for several decades FSCV studies have provided subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 164 publications
0
8
0
Order By: Relevance
“…The measurements were performed in the dorsolateral striatum, which receives dense innervation from the substantia nigra pars compacta of the brainstem. This brain area has been assessed for dopamine release using FSCV. , Initially, to test the feasibility of aptamer-modified nanopipettes for dopamine detection in brain slices, a strong high frequency stimulus (HFS) was employed in the dorsolateral striatum to maximize dopamine release (4 trains, 100 Hz, 9 mA stimulus). In repeated measurements, we observed that the 9 mA stimulus inducing brain contractions caused movement and subsequent misalignment of the inserted capillaries.…”
Section: Resultsmentioning
confidence: 99%
“…The measurements were performed in the dorsolateral striatum, which receives dense innervation from the substantia nigra pars compacta of the brainstem. This brain area has been assessed for dopamine release using FSCV. , Initially, to test the feasibility of aptamer-modified nanopipettes for dopamine detection in brain slices, a strong high frequency stimulus (HFS) was employed in the dorsolateral striatum to maximize dopamine release (4 trains, 100 Hz, 9 mA stimulus). In repeated measurements, we observed that the 9 mA stimulus inducing brain contractions caused movement and subsequent misalignment of the inserted capillaries.…”
Section: Resultsmentioning
confidence: 99%
“…Emergence of the hypodopaminergic state of the mesolimbic pathway in the early phase of the disorder might therefore lead to aberrant enhanced DA phasic signaling in the NAc, that would contribute to aberrant learning [56] and sensitization of the mesolimbic DA pathway to drugs or associated cue [57,58]. Within this framework, complex interplay between DA tone and DA phasic signals has already been reported using voltametric and microdialysis approaches, where chronic substance use persistently decreased DA tone while, in parallel, increased DA phasic responses to salient stimuli, thereby increasing "signal-to-noise" ratio in the NAc [59][60][61][62]. In addition, optogenetic studies conducted within the mesolimbic pathway have shown that increasing DA phasic firing promotes excessive alcohol seeking, whereas increasing DA tonic firing decreases consumption and abolishes the effect of DA phasic signal when induced simultaneously [12,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…This may impact the processes of synthesis, autoreceptor regulation of neurotransmitter release and reuptake. For example, the acceleration in dopamine uptake presumably due to the persistently elevated dopamine concentration in dopamine terminals was found using different models of drug addiction [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these changes can be protective or adaptive in nature, while other may play a significant role in the development of dysfunctions followed by the progression to diseases [1,3,5,[8][9][10][11][12]. The stressed-derived aberrations in the dopamine transmission have received particular attention due to the involvement of this neurotransmitter in pathological conditions, such as drug and alcohol addictions [8,13,14], anxiety, depression [15,16], and post-traumatic stress disorder (PTSD) [17][18][19][20]. In fact, these psychopathologies may be significantly escalated by chronic as well as by single exposure to stress [3,21,22].…”
Section: Introductionmentioning
confidence: 99%